DISCOURSE ON FEMALE IMAGES IN VICTORIAN LITERATURE - Mukhammedova Khulkar (Scholars Digest Publishing, 2024)
This article examines characters of Charles Dickens’s works. Charles Dickens described different women characters in his novels, in our point of view women, who clearly played an important role in his emotional history. Whole series of female characters play a dominant role in his novels’ development. In ‘Dombey and Son’ the author shows us the painfulness of Florence position as a daughter in the house of great capitalist. According to the typology we analyze features of Dickens’s female characters and divide them into types.
Keywords: analysis, novel, character, women, typology, literature, work.